Predictive Value of Preoperative Hematologic Inflammatory Markers in Prognostic of Glioma Patients - YU Xuedi (Zhongliu Fangzhi Yanjiu, 2019)
Objective To explore the predictive value of pre-operative hematologic inflammatory markers NLR, MLR and PLR in the clinical prognosis of glioma patients. Methods We enrolled 180 patients with glioma. ROC curve was used to determine the optimal cutoff values of NLR, MLR and PLR and we divided groups accordingly. The differences of parameters were analyzed by χ2 test. The Kaplan-Meier and Log rank methods were used to analyze patients' survival after operation. The independent prognostic factors were evaluated by multivariate Cox regression analyses. Pearson's correlation coefficient tested the correlations among these hematologic inflammatory markers. Results The optimal cutoff values of NLR, MLR and PLR were 1.90, 0.33 and 133.38, respectively. The median overall survival time of the patients with high NLR and MLR were 16.8 and 14.8 months, and those with low NLR and MLR were 40.5 and 24.6 months, respectively (all P < 0.05). The median tumor recurrence time were 10.3 and 28.8 months in the high and low NLR groups, respectively (P=0.002). NLR was an independent risk factor for glioma patients (HR=1.725; 95%CI: 1.042-2.853; P=0.034). NLR was correlated with MLR (r=0.62; P < 0.001) and PLR (r=0.59; P < 0.001). Conclusion Preoperative high NLR and MLR are related to poor prognosis of patients with glioma, and NLR is an independent prognostic factor and closely related to tumor recurrence rate.